2018
DOI: 10.14569/ijacsa.2018.090814
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Cloud Computing Adoption Framework for Iraqi e-Government

Abstract: Abstract-This paper presents an analysis of the factors which could have possible affect over the adoption of cloud computing via the Iraqi e-government. A conceptual framework model for cloud computing within Iraqi e-government is proposed, analyzed, evaluated and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…A framework for cloud adoption evaluating the procedure and factors for adoption was discussed in a study (Junior et al, 2020;Shukur et al, 2018). From this study, it was seen that very few studies adopted a framework.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A framework for cloud adoption evaluating the procedure and factors for adoption was discussed in a study (Junior et al, 2020;Shukur et al, 2018). From this study, it was seen that very few studies adopted a framework.…”
Section: Discussionmentioning
confidence: 99%
“…• Cost reduction-cloud computing is anticipated to reduce the cost of acquiring physical hardware, hence saving financial resources for organizations (Ali et al, 2015;Lian, 2015;Shukur et al, 2018). Accordingly, cost reduction is a promise achieved by adopting cloud services in organizations with a positive influence (Aziz et al, 2013;Kuiper et al, 2014;Mohammed & Ibrahim, 2015a;Mohammed & Ibrahim, 2015b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang, et al, [29] examined the barriers and benefits of CBEG for organisational use and concluded that the organisational, environmental and technological characteristics affect the usage of CBEG. In Iraq, [11] examined the usage of CBEG and proposed a conceptual framework for decision makers that includes the technological, environmental and organisational contexts and ease of use and legal issue. In this study, the TOE is examined, and it includes the technological, environmental and organisational perspectives.…”
Section: Toementioning
confidence: 99%
“…Cloud computing (CC) has emerged during the last decade, and it provides several advantages for individuals, organisations and government. This initiative can be the solution that the government is looking for to reduce the cost of operating E-government and enhance the services and efficiency of the governmental services [11]. Understanding the predictors of CC usages could help in securing a smooth shift from traditional E-government to CBEG.…”
Section: Introductionmentioning
confidence: 99%